The impact of tick control on the productivity of indigenous cattle under ranch conditions in Uganda - Okello-Onen, Joseph; Tukahirwa, E.M.; Perry, Brian D.; Rowlands, G.J.; Nagda, S.N.; Musisi, G.; Bode, E.; Heinonen, R.; Mwayi, W.; Opuda-Asibo, J. (Springer, 2003)
The impact of tick control on the productivity of indigenous cattle was investigated in three herds of East African shorthorn Zebu and Zebu×Ankole (Nganda) breeds, maintained under three tick management systems practised under ranch conditions: twice-a-week dipping, once-a-month dipping, and no tick control. The milk production and the growth rates of pre-weaned and post-weaned calves were monitored once a month over a period of 34 months. Milk offtake was 23% higher during the heavy rainy seasons than in the long dry seasons. Twice-a-week dipping increased the milk offtake by 21% in the second year of study and prolonged the duration of lactation in cows. Similarly, twice-a-week dipping increased the pre-weaning growth rate by 39% in the second year of study, but had no significant effect on the post-weaning growth rate. Generally, the growth rate of calves were greatest during the heavy rainy seasons and least during the long dry seasons. These results provide a basis for assessing the losses under different tick management systems in the various production systems.